2015
DOI: 10.1007/s12032-015-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sushi repeat-containing protein X-linked 2 is associated with progression of colorectal cancer

Abstract: Sushi repeat-containing protein X-linked 2 (SRPX2) is a novel chondroitin sulfate proteoglycan overexpressed in gastrointestinal cancer. Its role in tumor biology remains unknown. The aim of this study was to investigate the expression of SRPX2 in colorectal cancer and its potential association with cancer progression. The expression of SRPX2 and its clinicopathological significance was evaluated using immunohistochemistry in a tissue microarray including 88 colon cancer and pairing normal tissues. The impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Tanaka et al (7) reported that SRPX2 increases FAK phosphorylation levels in several gastric cancer cells. Gao et al (9) also found that the increase in SRPX2 is associated with FAK phosphorylation in pancreatic cancer tissue. In this study, FAK phosphorylation in HUVECs after addition of SRPX2 recombinant protein for 4.0 h was investigated.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Tanaka et al (7) reported that SRPX2 increases FAK phosphorylation levels in several gastric cancer cells. Gao et al (9) also found that the increase in SRPX2 is associated with FAK phosphorylation in pancreatic cancer tissue. In this study, FAK phosphorylation in HUVECs after addition of SRPX2 recombinant protein for 4.0 h was investigated.…”
Section: Resultsmentioning
confidence: 92%
“…The overexpression vector of pcDNA3.1(+)-SRPX2 plasmid and empty plasmid vector as control were constructed and transfected into SW480 (ATCC, Manassas, VA, USA) as previously described (8). SRPX2-CM was prepared according to Tanaka et al (10).…”
Section: Srpx2 Recombinant Protein and Srpx2-conditioned Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…[9] In addition, emerging studies have indicated that SRPX2 plays a critical role in tumorigenesis. [13] However, the role of SRPX2 in prostate cancer has not yet been reported. [13] However, the role of SRPX2 in prostate cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%